Oportunidad para presentar tercería excluyente de dominio en el procedimiento ejecutivo - Vargas Macas, Amy Mishell (2025)
The executive procedure is fundamental for debt collection but poses challenges in protecting third-party rights. The exclusionary third-party claim of ownership allows individuals not involved in a debt to defend their assets mistakenly seized. However, the current regulations established under the COGEP present ambiguities that limit the effectiveness of this mechanism, resulting in infringements on constitutional rights and complicating the defense of third-party rights. This study aims to analyze the relevance of the exclusionary third-party claim of ownership in executive procedures to prevent violations of constitutional rights. The research adopted a qualitative approach, using a non-experimental, cross-sectional design. Semi-structured interviews were conducted with judges and lawyers in Santo Domingo. An inductive-deductive method was applied, combining data collection with document analysis to interpret findings and draw conclusions about best practices and existing challenges. The results revealed a lack of uniformity in the application of the regulations and a recurring violation of fundamental rights, particularly the right to property, in cases where precautionary measures, such as seizures or attachments, are applied disproportionately or unjustifiably. Additionally, violations of the right to effective judicial protection were identified. The research emphasizes the importance of a systematic approach to the interpretation and application of regulations to ensure equitable and effective justice.